HARMONIZING DIVERSITY: CULTURALLY RESPONSIVE TEACHING STRATEGY FOR ELEVATING SPEAKING PROFICIENCY - Reskyani, Reskyani; A, Nasrullah; Mustaqimah, Mustaqimah; Adisaturrahimi, Andi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research aims to determine harmonizing diversity: culturally responsive teaching strategy for elevating speaking proficiency in speaking classes. This research used a qualitative descriptive method and in analyzing the data researchers used a thematic analysis to group them based on the strategies used by lecturers to improve students’ speaking. The data was found by researchers by conducting interviews with 3 different lecturers and implementing culturally responsive teaching in speaking classes. The results found by the researchers that there were 5 strategies and each strategy has several elements. There were 5 strategies, namely 1. Introduction and understanding of students’ cultural backgrounds, 2. Strategy for Integrating Multicultural Content, 3. Create a classroom environment that supports and respects diversity, 4. Activities or Projects to Encourage Students to Speak about Their Culture, 5. Assessment of Speaking Skills by Considering Cultural Diversity and several elements, namely 1. Initial Information Gathering and Personal Approach, 2. Use of Multicultural Materials and Direct Interaction, 3. Building an Inclusive Climate and Cultural Celebration, 4. Personal Cultural Expression and Interactive Method, 5. Inclusive Assessment and Constructive Feedback. With this strategy, it can be said that students’ speaking improves because the materials are based on their cultural background so it is easy for them to express what they want to say when speaking with their classmates, during group discussions, or talking together with their lecturers in class when the teaching and learning process is taking place.